Fatigue design of steel and composite structures : Eurocode 3: design of steel structures ; part 1 - 9: fatigue ; Eurocode 4: design of composite steel and concrete structures / Alain Nussbaumer; Luís Borges; Laurence Davaine - Nussbaumer, Alain1964-
Mua